AN ANALYSIS ON FAIRCLOUGH’S CRITICAL DISCOURSE ANALYSIS MODEL ON LYRICS OF SONG ENTITLED “TO THE BONE” - Daniel Ganda Putra Sihombing; Laura Leontina Manalu; Sara Sianipar; Cindya Septiany Simanjuntak; Indah Rumondang Manik; Herman Herman (Sean Institute, 2023)
The purpose of this study is to analyze how the role or attitude of the researcher towards the song appears in the study of influence, appreciation and recognition. The researcher used descriptive qualitative method by using three analytical processes proposed by Fairclough's CDA model. The research data is the lyrics of the song Pamungkas “To the Bone”. The findings show that Pamungkas clearly describes his feelings using the speech patterns in this song. Pamungkas in his song conveys how much he loves this woman, in other words he is ready to do anything to love the woman he likes. From an appreciative perspective, Pamungkas tries to indirectly convey how deep his feelings are for the woman he loves. Pamungkas then implicitly conveys in a moral assessment that love must be done in earnest. Based on his confession, Pamungkas conveyed through the lyrics of the song that love must be fought for and he does not know the word surrender